2017
DOI: 10.1002/pbc.26488
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and surveillance for reduced bone mineral density in pediatric cancer survivors

Abstract: The highest risk factors for low BMD were male gender, exposure to TBI, cranial, or craniospinal radiation, and gonadal dysfunction. Survivors receiving methotrexate or HCT therapy have the lowest risk for low BMD among those screened. Future studies should investigate risk of low BMD for survivors receiving HCT without radiation exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 52 publications
1
19
0
Order By: Relevance
“…In CCS treated with cranial irradiation, we found lower BMD at the total hip and lumbar spine, which is in line with previous studies [7,8,26]. Cranial irradiation in children is a known risk factor for later pituitary malfunctions [31], among others, growth hormone deficiency (GHD) and hypogonadism.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In CCS treated with cranial irradiation, we found lower BMD at the total hip and lumbar spine, which is in line with previous studies [7,8,26]. Cranial irradiation in children is a known risk factor for later pituitary malfunctions [31], among others, growth hormone deficiency (GHD) and hypogonadism.…”
Section: Discussionsupporting
confidence: 91%
“…Among adult childhood cancer survivors (CCS), almost 40% in the large St Jude Lifetime Cohort Study had low BMD in total body or lumbar spine [5]. Hypogonadism has been stated to be a risk factor of low BMD in CCS [6][7][8]. Available studies reporting on the association between hypogonadism and BMD in CCS are based on a low number of subjects [9][10][11], mixing both male and female CCS [8,[10][11][12] or lacking controls [8,9,11], making conclusions regarding possible association between hypogonadism and BMD in adult male CCS difficult.…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that methotrexate lowers BMD but does not present a significant risk for z-score ≤-2. 25) Hematopoietic stem cell transplantation (HSCT) also affects BMD. Bone loss occurred and continued frequently in the first year following allogeneic HSCT.…”
Section: Causative Factors Of Low Bmd In Children and Adolescents Witmentioning
confidence: 99%
“…Decreased BMD is a well‐known complication following cancer therapy and HSCT . Despite well‐documented decreases in BMD and diminished bone health in HSCT patients, it is unclear whether a significant increase in overall fracture risk ensues . However, vertebral fractures are becoming increasingly recognized, and these underappreciated fractures may be significantly related to decreased BMD …”
Section: Late Effects On the Vertebrae And Bmdmentioning
confidence: 99%
“…[44][45][46] Despite well-documented decreases in BMD and diminished bone health in HSCT patients, 41,[44][45][46] it is unclear whether a significant increase in overall fracture risk ensues. 44,45 However, vertebral fractures are becoming increasingly recognized, and these underappreciated fractures may be significantly related to decreased BMD. 27,47 Vertebral endplate deformity and compression fractures in HSCT and TBI patients may be more common than previously appreciated.…”
Section: Introduction and Epidemiologymentioning
confidence: 99%